Drugs in therapy. LSD, MDMA, marijuana, psilocybin, designer drugs and its potential in modern medicine. - Agata Tadeja (Farmacja Polska, 2020)
Research on using drugs in medicine was almost completely stopped and delegalized in 1971, by Convention on Psychotropic Substances. Most of studies carried out before 1971 were methodologically inappropriate according to current research methodologies, yet it was proven that there is some potential in using substances like lysergic acid diethylamide, 3,4-methylenedioxymethamphetamine, marihuana or psilocybin in treating some disorders, especially psychiatric disorders. Currently, there are being performed studies on influence of using drugs in many health problems. Therapy with psilocybin, seems perspective on people with anxiety, depression or other drugs abuse. This kind of therapy (psilocybin therapy) is always parallel to psychotherapeutic sessions. Similar results are observed in therapies using lysergic acid diethylamide on patients with terminal cancer stadium or drug addicts. 3,4-methylenedioxymethamphetamine could have a positive effect on people with post-traumatic stress disorder or social fears linked with adult autism in situation there is no effect after using classical therapies. Using of Cannabis sativa L. in different forms has a proven and broad positive effect in medical treatment of: post-traumatic stress disorder, epilepsy, neurological pain and many cutaneous conditions. A very wide source of potential new medicines could be a psychoactive substance group called designer drugs (or legal highs), which mimic effects of using well known classical drugs. Currently, new psychoactive substances are being developed in a very fast and massive way with biological impact very hard to predict and estimate. Basing on structural studies and effects described by people using them, some of those new designer drugs can have interesting positive properties like: weight reduction or reducing anxiety. The biggest challenge it is to properly verify and test, if drug therapy (lysergic acid diethylamide, 3,4-methylenedioxymethamphetamine, marihuana, psilocybin or designer drugs) can be safe for patients and as effective as standard therapies. Testing and estimating proper safe dosage and effective for the patient will be the most challenging. Further research and analysis should be taken on wider group of patients to expand the knowledge of this field of medical science.